2001
DOI: 10.1038/86342
|View full text |Cite|
|
Sign up to set email alerts
|

A CD14-independent LPS receptor cluster

Abstract: Bacterial lipopolysaccharide (LPS), the major structural component of the outer wall of Gram-negative bacteria, is a potent initiator of an inflammatory response and serves as an indicator of bacterial infection. Although CD14 has been identified as the main LPS receptor, accumulating evidence has suggested the possible existence of other functional receptor(s). In this study, using affinity chromatography, peptide mass fingerprinting and fluorescence resonance energy transfer, we have identified four new prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
315
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(331 citation statements)
references
References 45 publications
14
315
2
Order By: Relevance
“…However, to our knowledge, none of these molecules is expressed in significant amounts on endothelium. Very recently, heat shock proteins 70 and 90, chemokine receptor 4, and growth differentiation factor 5 have been reported to form a CD14-independent activation cluster after LPS ligation and are involved in LPS signal transduction (54). However, no mention of a need for TLR4 was made in that study.…”
Section: Discussionmentioning
confidence: 86%
“…However, to our knowledge, none of these molecules is expressed in significant amounts on endothelium. Very recently, heat shock proteins 70 and 90, chemokine receptor 4, and growth differentiation factor 5 have been reported to form a CD14-independent activation cluster after LPS ligation and are involved in LPS signal transduction (54). However, no mention of a need for TLR4 was made in that study.…”
Section: Discussionmentioning
confidence: 86%
“…Hsp60 might signal through CD14, TLR-2 and TLR-4 [61,62], probably binding to a different molecule [63]. It was also suggested that Hsp90 and Hsp70 bound to LPS [64,65], and the latter could activate the innate immune response by a TLR4-mediated signal pathway [66]. In fish, beta-propiolactone (BPL) e inactivated VHSV was able to activate the expression of genes involved in the innate immune response in vitro [67], and some genes related to early immune response, such as IL-1b, TGF-b, IL-8 and iNOS, were simultaneously up-regulated in rainbow trout challenged with VHSV [68].…”
Section: Discussionmentioning
confidence: 99%
“…Hsp60 was active at concentrations of 0.1 to 1.0ng/ml (approximately 0.1-1.0pM) but not active in the range 10-100ng/ml but again active at concentrations of 1µg/ml. One possible explanation is the involvement of different receptors with different affinities or of some form of receptor activation complex such as is postulated for LPS [70]. A fascinating suggestion is that Hsp60 acts as a co-stimulator of human T-regulatory cells (Tregs).…”
Section: Hsp (Chaperonin)60mentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w proteins including Hsp70. The other members of this so-called LPS activation complex are Hsp90, CXCR4 and growth differentiation factor (GDF)5 [112,113]. Other workers have reported that Hsp70 members in plasma membranes act as 'receptors' for viruses.…”
Section: Plasma Membranementioning
confidence: 99%